Pengaruh Model Pembelajaran SAVI (Somatic, Auditory, Visualization And Intellectualy) dalam Meningkatkan Pemahaman Siswa: The Effect of SAVI Learning Model (Somatic, Auditory, Visualization And Intellectualy) in Improving Student Understanding - Sohim, Badru; Saputra, Ajat; Agustian, Rijal; Setiawan, Iwan; Aji Kurniawan, Tri (CV. Kalimasada Group, 2023)
This study aims to determine the effect of the SAVI (Somatic, Auditory, Visualization and Intellectual) learning model in improving student understanding of PAIBP subjects in class X students of the TKJ A department at SMK Nurul Huda Sagalaherang. treatment. The population in this study were all students of Class X SMK Nurul Huda Sagalaherang in the odd semester of the 2022/2023 academic year which consisted of 6 classes and 1 class was chosen randomly as the research sample. Data were collected using observation sheets on the implementation of learning, learning outcomes tests (pretest and posttest), student activity observation sheets, and student response questionnaires. The data analysis technique used is descriptive statistical analysis technique. The results of descriptive statistical analysis showed: (1), the reality of student understanding based on the posttest analysis, the results obtained obtained a value of 15.72 which included a scale criterion between 14.00 to 16.00 with good information (2), the effect of the SAVI learning model in improving understanding students in PAIBP subjects based on the analysis of the normalized n-gain average of 0.39 (medium category). (3), the value of correlation analysis obtained the value of Sig. (2-tailed) 0.000. Because the value of Sig (2-tailed) < 0.05, it can be interpreted that there is a significant relationship between the X and Y variables. Class X students majoring in TKJ A at SMK Nurul Huda Sagalaherang.